Prostate Cancer Screening: Is it Recommended in 2024? - Dr. Ali Thwaini (مجلة كلية الطب)
As we are living the month of Men’s Health awareness, November, we thought of touching base regarding screening for prostate cancer; an intriguing topic indeed, and the jury is out as of yet regarding whether to formalize a screening platform for prostate cancer.